Optimizing Capital Management in Baitul Maal wat Tamwil: Issues and Approaches - Rohman, Pupun Saepul; Laila, Nisful; Fianto, Bayu Arie; Ascarya, Ascarya; Rusydiana, Aam Slamet (Economica: Jurnal Ekonomi Islam, 2024)
Baitul Maal wat Tamwil (BMT) is a microfinance institution operating under Sharia principles, integrating social welfare and commercial finance to promote poverty alleviation and economic empowerment. Despite its potential, BMTs face significant capital challenges that hinder their sustainability and impact. This study explores these challenges using a qualitative methodology with a literature review approach. Six key issues are identified: (1) limited capital from low member savings, (2) inadequate accumulation of social funds, (3) mismatch between available funds and customer needs, (4) reliance on external funding, (5) low business volume, and (6) weak integration between the social (Baitul Maal) and commercial (Baitul Tamwil) functions. These issues restrict BMTs from fully achieving their financial inclusion and social welfare objectives. To address these challenges, the study suggests optimizing low-cost funds, managing cash waqf, strengthening Baitul Maal, collaborating with zakat institutions, and integrating Islamic social finance with commercial operations. Additionally, increasing principal and mandatory savings is recommended to improve capital stability. Resolving these issues is essential for enhancing BMTs' role in poverty alleviation and ensuring their long-term sustainability and effectiveness within the Islamic finance framework.